Solidarity and inclusion on EU citizens in the member states The changing jurisprudence of the ECJ in light of economic challenges - Farahat, Anuscheh (Revista general de derecho público comparado, 2018)
The solidarity dimension of EU citizenship has recently been hotly debated in legal literature and jurisprudence. Excluding job seekers of other EU Member States from social security has provoked a number of recent judgements by the European Court of Justice. In this jurisprudence the dimensions of inclusion and solidarity of EU citizenship have been renegotiated. This article examines the crucial doctrinal and conceptual changes that EU citizenship has undergone through this jurisprudence and assesses its consequences for the concept of a free and equal citizenship in Europe in the future. The article focuses particularly on the role of domestic constitutional law in the future shaping of social rights attached to EU citizenshi
Keywords: Solidarity and inclusion on EU citizens in the member states